2018
DOI: 10.1038/s41598-018-31288-7
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS1 protease is required for a balanced immune cell repertoire and tumour inflammatory response

Abstract: Recent advances have emphasized the relevance of studying the extracellular microenvironment given its main contribution to tissue homeostasis and disease. Within this complex scenario, we have studied the extracellular protease ADAMTS1 (a disintegrin and metalloprotease with thrombospondin motif 1), implicated in vascularization and development, with reported anti- and pro-tumorigenic activities. In this work we performed a detailed study of the vasculature and substrates in adult organs of wild type and Adam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Indeed, our data with SwN mice disclosed a complete halt using ATS1-KO cells, which was partially overcome using an NSG model. Importantly, the immune system of NSG mice displays a stronger defect than SwN, so the distinct ability of ATS1-KO cells to initiate tumor progression in these two models could be related with an immunomodulatory role already attributed to ADAMTS1 [11]. Certainly, these results encourage further studies to unveil the impact of this ECM-modifying enzyme on the immune system, although distinct models must be considered.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Indeed, our data with SwN mice disclosed a complete halt using ATS1-KO cells, which was partially overcome using an NSG model. Importantly, the immune system of NSG mice displays a stronger defect than SwN, so the distinct ability of ATS1-KO cells to initiate tumor progression in these two models could be related with an immunomodulatory role already attributed to ADAMTS1 [11]. Certainly, these results encourage further studies to unveil the impact of this ECM-modifying enzyme on the immune system, although distinct models must be considered.…”
Section: Discussionmentioning
confidence: 91%
“…All these data confirmed the relevance of ADAMTS1 for tumor development. Since previous findings already remarked its effect on the vasculature [9,11,24], we analyzed it in our NSG samples. Endomucin (EMCN) IF revealed an increased vessel density but a reduction in perimeter in tumors derived from ATS1-KO cells (Figure 3e,f), resulting in a lack of significant differences in terms of total vessel area between WT and ATS1-KO tumors (Figure 3f), as previously described in other tumor studies [6,9].…”
Section: Adamts1 Inhibition Affects In Vivo Tumor Progression and Vasmentioning
confidence: 99%
See 2 more Smart Citations
“…ADAMTS1 expression was dysregulated in primary gastric cancer and paired lymph node metastasis [38]. Recent study found that ADAMTS1 was required for a balanced immune cell repertoire and tumor inflammatory response via affecting lymphocyte and myeloid populations in the spleen and bone marrow [39]. In the present study, we analyzed the correlations between OGN, JAM2, RERG, OLFML2B, and ADAMTS1 expressions and clinical characteristics (clinical stage, grade, N stage, T stage, and H. polyri infection) (Supplementary Figure S1).…”
Section: Discussionmentioning
confidence: 99%